Medication non‐adherence after allogeneic hematopoietic cell transplantation in adult and pediatric recipients: a cross sectional study conducted by the Francophone Society of Bone Marrow Transplantation and Cellular Therapy. (7th January 2021) - Belaiche, Stephanie; Décaudin, Bertrand; Caron, Alexandre; Depas, Nicolas; Vignaux, Claire; Vigouroux, Stephane; Coiteux, Valérie; Magro, Leonardo; Sirvent, Anne; Huynh, Anne; Turlure, Pascal; Farge, Dominique; et al.
Abstract: Medication non‐adherence (NA) after allogeneic hematopoietic cell transplantation (allo‐HCT) can lead to serious complications. This study assesses NA in French adult and pediatric recipients and identifies factors associated with NA. In accordance with the EMERGE and STROBE guidelines, a cross sectional multicentric survey was conducted. We used a self‐reported questionnaire that was adapted to adults and pediatrics and that could provide a picture of all three phases of medication adherence: initiation, implementation, persistence. We enrolled 242 patients, 203 adults (mean age: 51 years old, 50.7% male) and 39 children (mean age: 9 years old, 56.4% female). Reported NA was estimated at about 75% in both populations, adults and pediatrics. In adults, the univariate analysis showed that patients less than 50 years old ( P = 0.041), (i) treated with cyclosporine ( P = 0.02), (ii) treated with valacyclovir/acyclovir ( P = 0.016), and (iii) experiencing side effects ( P = 0.009), were significantly more non‐adherent. In multivariate analysis, only recipient age was significantly associated to NA ( P = 0.05). The limited size of the pediatric population did not allow us to draw any statistical conclusion about this population. To the best of our knowledge, this is the first study in France on NA in allo‐HCT recipients. Our results highlight the age factor as the only factor related to NA. Further studies are needed to confirm our observations and refine results in pediatric populations, currently most at risk of medication NA.